2017
DOI: 10.1002/pbc.26844
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive outcomes among Latino survivors of childhood acute lymphoblastic leukemia and lymphoma: A cross‐sectional cohort study using culturally competent, performance‐based assessment

Abstract: Similar to other childhood ALL/LL survivors, overall cognitive function in this Latino sample was relatively preserved but selected deficits were observed. Routine cognitive screening is indicated in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Study procedures have been previously described. 18 In brief, as part of their cancer survivorship clinic initial evaluation, survivors of childhood ALL/LL routinely undergo neurocognitive assessment based upon a combination of the Children's Oncology Group Long-term Follow-up Guidelines 19 and programmatic standards. 20 Participants were recruited from the survivorship clinic and provided informed consent/assent.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Study procedures have been previously described. 18 In brief, as part of their cancer survivorship clinic initial evaluation, survivors of childhood ALL/LL routinely undergo neurocognitive assessment based upon a combination of the Children's Oncology Group Long-term Follow-up Guidelines 19 and programmatic standards. 20 Participants were recruited from the survivorship clinic and provided informed consent/assent.…”
Section: Methodsmentioning
confidence: 99%
“…This cross‐sectional study represents a secondary analysis focused on language proficiency including data previously reported on neurocognitive outcomes using standardized performance‐based measures 18 . This study sample was nested in a cancer survivorship research database approved by the Institutional Review Board and registered on ClinicalTrials.gov (NCT01518400).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, limited research examines functional outcomes, or long‐term outcomes more generally, in racial or ethnic minority survivors of pediatric brain tumor despite widespread recognition of the need for such studies . Two studies have reported neurocognitive and psychosocial outcomes among cohorts of Latino/Hispanic survivors of acute lymphoblastic leukemia. In fact, the most recent studies of adaptive functioning in survivors of pediatric brain tumor do not report on the ethnic or racial make‐up of the sample and exclude non‐English‐speaking families from participation …”
Section: Introductionmentioning
confidence: 99%